Microwave-assisted synthesis of ZnO for photocatalytic reduction of Cr(VI) in aqueous solution - Liu, Xinjuan (2013)
ZnO sheets have been synthesized via microwave-assisted reaction of ZnO precursor in aqueous solution using a CEM microwave system. Their morphologies, crystal structures and photocatalytic performances in the reduction of Cr(VI) were characterized using scanning electron microscopy, transmission electron microscopy, X-ray diffraction spectroscopy and UV-vis absorption spectrophotometer, respectively. Results show that ZnO sheets synthesized in 5 min time scale exhibits a optimal photocatalytic performance in the reduction of Cr(VI) with removal efficiency of 81% under UV irradiation due to the maximal intensity of light absorption and the minimal probability of electron-hole pair recombination.